2015
DOI: 10.2519/jospt.2015.5712
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Meniscal Tears in Primary Care: Reproducibility and Accuracy of 2 Weight-Bearing Tests and 1 Non–Weight-Bearing Test

Abstract: Diagnosis, level 3b.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 27 publications
(56 reference statements)
0
10
0
Order By: Relevance
“…Also, mechanical symptoms, when present, do not arise exclusively from meniscal tears and may be positive in other disorders such as ACL tear or osteoarthritis [3,6]. This adds to the growing evidence suggesting that these history elements and tests may have limited diagnostic value, as well as a possibly limited use as a surgical criterion [3,10,16,18‐20,22,23,49,52‐55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, mechanical symptoms, when present, do not arise exclusively from meniscal tears and may be positive in other disorders such as ACL tear or osteoarthritis [3,6]. This adds to the growing evidence suggesting that these history elements and tests may have limited diagnostic value, as well as a possibly limited use as a surgical criterion [3,10,16,18‐20,22,23,49,52‐55].…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation for this overreliance on MRI is that the diagnostic validity of physical examination tests presents conflicting results [16]. Based on low‐grade evidence, most commonly studied clinical tests (ie, joint line tenderness test, McMurray test, Apley maneuver, and the Thessaly test) are not able to accurately diagnose or exclude SMT when used individually [16‐20]. Yet, it is often reported that medical specialists or physiotherapists with extensive training and expertise in musculoskeletal disorders can make an accurate clinical diagnosis of a SMT based on a complete physical examination combined with the patient's history.…”
Section: Introductionmentioning
confidence: 99%
“…However, this has not resulted in improved diagnostic accuracy when compared with nonweight-bearing tests and has also demonstrated a wide variation in sensitivity (53-97%) and specificity (38-98%). [19][20][21][22] Imaging Rationale and Justification Health care expenditure in the United States continues to rise each year at a rate of 3 to 4% and accounts for 17% of the annual economy. 23 Conditions resulting in joint pain and arthritis account for approximately $200 billion annually and are estimated to affect more than 100 million individuals in the United States.…”
Section: Meniscal Evaluationmentioning
confidence: 99%
“…Deep Squat Test (DS) is one of tests of the Functional Movement Screen™ (FMS™) [1] and Dynamic Movement Assessment™ (DMA™) [2], tools to classify the risk of musculoskeletal injuries. DS has been applied in preseason evaluations of sports teams [3 -5] and in military courses [6]. It is considered the test that predict the risk score at FMS™ [3].…”
Section: Introductionmentioning
confidence: 99%